KEDUDUKAN PEREMPUAN SEBAGAI KEPALA KELUARGA DI KELURAHAN CENGKARENG BARAT, KECAMATAN CENGKARENG, JAKARTA BARAT: Women's Position as Head of Family in Cengkareng Barat Urban Village, Cengkareng Sub-district, West Jakarta - Nabila Febrita; Wahyuni Retnowulandari (Reformasi Hukum Trisakti, 2025)
Women today undeniably have a role as workers to fulfil family income, even becoming the backbone of the family. Women are now able to do many things and have an important role to support the family financially. In Cengkareng Barat Urban Village, Cemgkareng Subdistrict, West Jakarta, there are quite a number of women found as heads of families. The identification of this research problem is how is the implementation of Article 16 of the Convention on the Elimintion of All Forms of Discrimination against Women (CEDAW) on women's rights as heads of households in RT. 08/RW.01 West Cengkareng Village, Cengkareng District, West Jakarta? This research uses socio-legal method and purposive random sampling method. The conclusion of the research shows that the implementation of Article 16 of CEDAW 1979 regarding women's rights in marriage and family relations in the area has not been implemented, even many female residents do not know/understand their rights in the family according to the article. The author also recommends that Article 31 paragraph (3) of the Marriage Law be revised so that there is no longer a need to differentiate between the position of husband and wife in a family.